CT parameters of psoas muscle predicts 28-day mortality in older patients with sepsis: a retrospective study - Yun Wang; Tun Zhao; Min Liu; Wenli Hu (BMC Geriatrics)
Abstract Odjectives To investigate the predictive value of computed tomography (CT)-based transverse diameter (TD) and longitudinal diameter (LD) of the psoas muscle at the level of third lumbar vertebra for 28-day mortality in older patients with sepsis. Methods This retrospective single-center cohort study included 115 septic patients aged over 65 years old who were admitted to ICU in Beijing-Chaoyang Hospital between July 2017 and July 2022. The TD and LD of psoas muscle were obtained by measurement on abdominal CT images. Logistic regression analysis was conducted to identify the prognostic factors for 28-day mortality in older patients with sepsis, and their predictive performances were evaluated using the receiver operating characteristic (ROC) curve. Results Multivariable logistic analysis indicated that TD (OR: 0.405, 95% CI: 0.190–0.864) was a protective factor for 28-day mortality in older patients with sepsis, whereas LD was not. The areas under the curve (AUCs) of TD, APACHE II, and SOFA were 0.666 (95% CI: 0.565–0.767), 0.660 (95% CI: 0.561–0.760), and 0.679 (95% CI: 0.581–0.777), respectively. Furthermore, the AUCs for the combination of TD with APACHE II or SOFA were 0.766 (95% CI: 0.679–0.853, P < 0.001) and 0.765 (95% CI: 0.679–0.852, P < 0.001). Conclusions TD of psoas muscle was a predictor for 28-day mortality in older patients with sepsis. The combination of TD with APACHE II or SOFA scores enhances the early identification of patients at high risk for poor prognosis. Clinical trial number not applicable.